Fiscal Decentralization, Fiscal Incentives, and Pro-Poor Outcomes: Evidence from Viet Nam - Liv Bjornestad (Asian Development Bank (ADB), 2009)
This paper provides an in-depth analysis of the relationship between fiscal decentralization and pro-poor outcomes based on the role of fiscal incentives. The literature on the relationship between fiscal decentralization and pro-poor outcomes is not well established in this area. A conceptual model is developed to explore in more detail this relationship, while endeavoring to illuminate the complexity of the issues involved for policy makers in developing countries. Four types of fiscal incentives are explored: namely, resources, responsibility, autonomy, and accountability. The paper then assesses the effectiveness of the Vietnamese system of fiscal decentralization for achieving pro-poor outcomes through a devolved system of fiscal incentives. The paper suggests that evidence from the Vietnamese case indicates that fiscal decentralization may contribute to poverty reduction outcomes, but does not provide evidence that fiscal decentralization is in and of itself inherently pro-poor. Rather, the lesson from Viet Nam is that if poverty reduction is an explicit objective for government, the system of fiscal decentralization should target pro-poor outcomes through an appropriate system of fiscal incentives. Since 2002, budgetary reallocation and income redistribution linked to poverty outcomes has been more strongly associated with equalizing fiscal transfers than with devolved finances in general. This represents a broadly correct approach to target poverty outcomes in a territorially unbalanced country like Viet Nam. Targeted transfers contribute to pro-poor outcomes by increasing the level of resources available to finance poverty spending. However, increasing the level of fiscal transfers for poverty spending will not ensure that fiscal transfers are then spent efficiently. In order to better realize these efficiency objectives, the government can promote greater fiscal and administrative decentralization of resources and responsibility to district- and commune-level governments. Further gains in this area must also be supported by greater levels of fiscal autonomy and fiscal accountability at the local government level.
hdl:11540/1817
Keywords: 330; Dezentralisierung; Armutsbekämpfung; Vietnam